Minimally invasive plate osteosynthesis (MIPO) for complete fracture of the tibia and fibula in canine (Canis lupus familiar): Virtual preoperative planning - Roberto Javier Lope-Huaman; Alexandra Curasco-Ayma; Javier Fernandez-Apaza (Journal of the Selva Andina Animal Science)
A clinical case study is presented to describe the use of the minimally invasive plate osteosynthesis (MIPO) technique, using the PRCL-M system with 11-hole locking compression and reconstruction plate with 6 locking screws. Virtual preoperative planning using the CorelDRAW version X5 vector program for digital design was employed to reduce the possible complications that could arise in an intervention. The subject was a 6-month-old male American Bull canine, presented with evident claudication in the right hind limb. Radiographic plates revealed a short oblique complete fracture at the proximal diaphysis of the right tibia and fibula, a low energy trauma occasioned by a motorcycle road traffic accident. This osteosynthesis case was resolved with OPMI. This minimally invasive technique is widely accepted for fractures of this nature, with satisfactory clinical results, owing to the flat surface of the medial border of the tibia. In this case, osteosynthesis and early healing resulted in a rapid recovery that was observed during postoperative care, without secondary complication